Fostering human rights and empowering communities through art and education: the case of the National Gallery of Zimbabwe - Chiwara, Davison (Taylor and Francis, 2021)
Articles 26 (1) (2) and 27 (1) of The United Nations Universal Declaration of Human Rights call for the right to education for everyone and state that everyone has a right to freely participate in cultural life of the community; and to enjoy the arts. In light of this, this paper examines the role of the National Gallery of Zimbabwe () in advancing these rights as an institution that promotes social inclusion. Research findings show that incorporates marginalised people in society, school children, students at tertiary institutions and the public at large in its educational activities. Consequently, these communities have formed art clubs and are undertaking artistic endeavours on their own.